(3TQM JTQjYGJ GdCMhGd GdTNUjI ddeUQjjf ZjQ GdeSdejf hGdCLGfHs explanation of personal statutes for non-muslim egyptians and for foreigners - (3eQGO, YHO GdaJGMs ((3GdCScfOQjI (B[(3eUQ(B]s [(3O(B. (3f(B]s)
(3TQM JaUjdj dfUhU GdbGfhf hGMO dSfI (B2000 (3hbhGfjf GdCMhGd GdTNUjI dZjQ GdeSdejf hGdCLGfH hJWHjbGJ GdfbV hGdOSJhQjIs
(3jTJed Ydi GQLGYGJ HHdjhLQGajIs
11
Keywords: (3GdCMhGd GdTNUjIs -- (3JTQjYGJs; (3GdCMhGd GdTNUjIs; (3RhGL ZjQ GdeSdejfs -- (3bhGfjfs